The effect of anti-corruption character education on educational integrity - Aida Ratna Zulaiha; Asep Herry Hernawan; Laksmi Dewi (Himpunan Pengembang Kurikulum Indonesia, 2025)
Anti-corruption character education is a strategic effort to create a generation with integrity. This study analyzes the outcomes of anti-corruption character education in formal education in Indonesia, focusing on honesty, responsibility, discipline, and independence. A survey conducted via WhatsApp Blast, CAWI, and CAPI, involving 57,611 students, university students, teachers, lecturers, and education personnel from 3,098 educational institutions, was carried out. The results indicate that students demonstrate a higher level of honesty in terms of not lying and cheating, while university students exhibit a higher level of honesty in terms of not falsifying data. Students display higher levels of responsibility and discipline compared to university students. Regarding independence, university students show lower results in terms of completing assignments without assistance, managing time effectively, and initiating tasks. This study highlights the crucial role of teachers, lecturers, school principals, and university leaders as role models in fostering these values. However, the role modeling of school principals and university leaders is relatively low, emphasizing the need for enhanced leadership integrity within educational institutions. This study underscores the importance of strengthening role modeling, integrating character values into the curriculum, improving the integrity of the education ecosystem, and promoting collaboration to create a generation with integrity. Abstrak Pendidikan karakter antikorupsi merupakan upaya strategis untuk menciptakan generasi yang berintegritas. Penelitian ini menganalisis outcome dari pendidikan karakter anti-korupsi pada pendidikan formal di Indonesia, dengan fokus pada kejujuran, tanggung jawab, kedisiplinan dan kemandirian. Survei melalui WhatsApp Blast, CAWI dan CAPI melibatkan 57.611 siswa, mahasiswa, guru, dosen dan tenaga kependidikan, dari 3.098 satuan pendidikan Hasilnya menunjukkan kejujuran siswa lebih baik pada aspek tidak berbohong dan tidak curang, sedangkan mahasiswa lebih baik pada aspek tidak memalsukan. Siswa memiliki tanggung jawab dan disiplin yang lebih tinggi dibandingkan mahasiswa. Terkait kemandirian, mahasiswa menunjukkan hasil lebih rendah dalam menyelesaikan tugas tanpa bantuan, mengatur waktu secara efektif, dan menunjukkan inisiatif dalam memulai pekerjaan. Penelitian ini menyoroti peran penting guru, dosen, kepala sekolah dan pimpinan universitas sebagai teladan dalam menumbuhkan nilai-nilai tersebut, namun, keteladanan kepala sekolah dan pimpinan universitas relatif rendah, menekankan perlunya peningkatan integritas kepemimpinan dalam lembaga pendidikan. Penelitian ini menggarisbawahi pentingnya memperkuat keteladanan, mengintegrasikan nilai-nilai karakter pada kurikulum, meningkatkan integritas ekosistem pendidikan, dan mendorong kolaborasi untuk menciptakan generasi berintegritas. Kata Kunci: Antikorupsi; pendidikan karakter; integritas; keteladanan